2021
DOI: 10.1097/bpo.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Coronal Imbalance and Shoulder Asymmetry Continue to Improve Between 2 and 5 Years Following Surgery of Adolescent Idiopathic Scoliosis

Abstract: Background: Managing patients with coronal imbalance (CI) and shoulder height asymmetry following scoliosis surgery can be challenging. Little is known about the course of findings over time and whether they improve or persist. The aim was to report the rate of suboptimal radiographic CI or shoulder asymmetry (SA) at 5 years in patients who were already reported to have CI or SA 2 years after surgery for adolescent idiopathic scoliosis (AIS). Methods: An AIS database was reviewed for patients with both 2-and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Given advancements in quality and safety, Mehta et al reviewed the rate of unplanned returns to the operating room for patients with adolescent idiopathic scoliosis undergoing spinal fusion and found that this rate decreased 0.46% per year from 1997 to 2013 12 . In a review of patients undergoing posterior spinal fusion, Hughes et al noted continued improvement from 2 to 5 years postoperatively with regard to the rate of coronal imbalance of >2 cm, which decreased from 17% to 6%, and shoulder asymmetry of >2 cm, which decreased from 8% to 1% 13 .…”
Section: Spinementioning
confidence: 99%
“…Given advancements in quality and safety, Mehta et al reviewed the rate of unplanned returns to the operating room for patients with adolescent idiopathic scoliosis undergoing spinal fusion and found that this rate decreased 0.46% per year from 1997 to 2013 12 . In a review of patients undergoing posterior spinal fusion, Hughes et al noted continued improvement from 2 to 5 years postoperatively with regard to the rate of coronal imbalance of >2 cm, which decreased from 17% to 6%, and shoulder asymmetry of >2 cm, which decreased from 8% to 1% 13 .…”
Section: Spinementioning
confidence: 99%